2011
DOI: 10.1007/s00421-011-2054-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity and oxygen uptake kinetics in African-American and Caucasian women

Abstract: The effect of exercise intensity on the on- and off-transient kinetics of oxygen uptake (VO2) was investigated in African American (AA) and Caucasian (C) women. African American (n=7) and Caucasian (n=6) women of similar age, body mass index and weight, performed an incremental test and bouts of square-wave exercise at moderate, heavy and very heavy intensities on a cycle ergometer. Gas exchange threshold (LTGE) was lower in AA (13.6±2.3mL·kg−1min−1) than C (18.6±5.6mL·kg−1min−1). The dynamic exercise and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…African American women possess lower cardiorespiratory fitness [ 14 , 15 ] and a higher prevalence of obesity [ 16 ] and insulin resistance [ 17 ] compared to their white counterparts and also tend to be less physically active [ 13 ]. To counteract the metabolic repercussions of these differences, lifestyle changes including caloric restriction and increased physical activity have been recommended [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…African American women possess lower cardiorespiratory fitness [ 14 , 15 ] and a higher prevalence of obesity [ 16 ] and insulin resistance [ 17 ] compared to their white counterparts and also tend to be less physically active [ 13 ]. To counteract the metabolic repercussions of these differences, lifestyle changes including caloric restriction and increased physical activity have been recommended [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to their white counterparts, African American (AA) women are less physically active with time constraints specifically cited most frequently as the reason [ 13 ]. African American women also possess lower cardiorespiratory fitness (e.g., maximal rate of oxygen uptake and lactate threshold) [ 14 , 15 ] and a higher prevalence of obesity [ 16 ] and insulin resistance [ 17 ] compared to their white counterparts The lower oxidative capacity demonstrated by AA individuals appears to be linked to an increased percentage of type II muscle fibers [ 18 ], which are serially recruited during physical activity based on intensity of effort [ 19 ]. Interestingly, it was recently shown that 6 weeks of HIIT performed by previously-sedentary women resulted in increases in capillary density and mitochondrial content in both principal fibre types [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…; Fawkner and Armstrong ; Lai et al. ). Nevertheless, in our study, τ 1 of adolescents appears closer to the adult rather than prepubertal children's response to both M and H. This could be related to the maturation level that was reported to affect V̇ O 2 kinetics (Babcock et al.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this subject population because AA women have a higher incidence of obesity (39) and metabolic inflexibility (7) and lower cardiorespiratory fitness (e.g., V O 2max and LT) (40,52), peripheral insulin sensitivity, and mitochondrial capacity (17) compared with their white counterparts. AA women are also less physically active, with time constraints being the most frequently cited reason (18).…”
mentioning
confidence: 99%